OSA Imaging and Applied Optics Congress 2021 (3D, COSI, DH, ISA, pcAOP) 2021
DOI: 10.1364/cosi.2021.cw5b.5
|View full text |Cite
|
Sign up to set email alerts
|

Depth Estimation of Non-line-of-sight Objects from Scattered Light Enhanced by the Infrared Light Field

Abstract: We experimentally demonstrate depth estimation of human temperature NLOS objects from infrared light scattered off a construction wall. The measured IR light field is used to enhance the weak scattered signature and to perform depth estimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, the performance of these methods is often compromised by the significant scattering produced by the rough surface of the wall and the visible ambient light. We and several authors have reported that the use of long-wave-infrared (LWIR) light has several advantages that can reduce these difficulties [16,[17][18][19][20]. First, thermally-elevated objects such as human subjects are seen as light emitters, and these signals stand out amongst the ambient background.…”
Section: Introductionmentioning
confidence: 99%
“…However, the performance of these methods is often compromised by the significant scattering produced by the rough surface of the wall and the visible ambient light. We and several authors have reported that the use of long-wave-infrared (LWIR) light has several advantages that can reduce these difficulties [16,[17][18][19][20]. First, thermally-elevated objects such as human subjects are seen as light emitters, and these signals stand out amongst the ambient background.…”
Section: Introductionmentioning
confidence: 99%